Analisis Pendapatan dan Belanja Menggunakan Aspek Value for Money - Gunawan, Barbara; Putriantoro, Alifia (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the performance of the realization of the revenue and expenditure budget of the Tourism Office of Sleman Regency by taking into account the level of economy, efficiency, and effectiveness of the allocation of funds to assess the budget. The object of this research is the Tourism Office of Sleman Regency which is located at Jl. KRT. Pringgodiningrat, Tridadi, Sleman, Yogyakarta with the main data source being the 2019 Budget Realization Report. This study uses a quantitative descriptive method with primary and secondary data types. This type of primary data was obtained through an interview process with the Finance, Planning and Evaluation Section of the Tourism Office of Sleman Regency. While secondary data comes from information that has been uploaded on the official website of the Sleman Regency Tourism Office. Data analysis uses Value For Money indicators, namely to determine the level of economy, efficiency, and effectiveness. The results of the calculation analysis for each level indicate that the revenue budget is included in the effective criteria. Meanwhile, the expenditure budget shows that it is quite economical and overall the Budget Realization Report shows very efficient results. The implication of this research is that in the future the Tourism Office of Sleman Regency will pay more attention to market prices and strategic plans in preparing the budget so that the difference between spending and income is not too large and detailing the elements of the two categories.